Increased Extracellular Matrix Metalloproteinase Inducer (EMMPRIN) Expression in the Conjunctival Epithelium Exposed to Antiglaucoma Treatments. (January 2015) - Labbé, Antoine; Gabison, Eric; Brignole-Baudouin, Françoise; Riancho, Luisa; Menashi, Suzanne; Baudouin, Christophe
Abstract Objective: To analyze the effect of preserved antiglaucoma eye drops on the expression of extracellular matrix (ECM) metalloproteinase inducer (EMMPRIN) in conjunctival epithelial cells. Methods: A total of 18 patients treated for primary open-angle glaucoma with benzalkonium chloride (BAK) preserved eye drops and eight age-matched controls were included in this study. Glaucoma patients were divided into two groups according to their daily exposure to BAK: high-exposure (HE) group and low-exposure (LE) group. HLA-DR and EMMPRIN were quantified on conjunctival impression cytology specimens using flow cytometry. In parallel, IOBA-NHC conjunctival epithelial cells were exposed to different BAK concentrations, in the presence or absence of cyclosporine A (CsA), and their total and surface expressions of EMMPRIN were assessed by flow cytometry and results are given in relative fluorescence intensities (RFIs). Results: Compared to the control group (1.71 ± 0.39 RFI), EMMPRIN was significantly increased in the HE (4.19 ± 1.50 RFI, p < 0.001) and LE groups (2.55 ± 0.40 RFI, p = 0.029). Similar increase was observed in HLA-DR expression in the HE (4.58 ± 1.38 RFI, p < 0.001) and LE groups (2.52 ± 0.47 RFI, p = 0.046) as compared to control subjects (1.75 ± 0.27 RFI). Across all subjects enrolled in the study, there was a significant correlation between HLA-DR and EMMPRIN (R2 = 0.875, p < 0.0001). IOBA-NHC cells exposed to BAK presented a significant increase in EMMPRIN, which was proportional to the concentration of BAK. The surface expression of EMMPRIN was inhibited by CsA. Conclusions: The increased expression of EMMPRIN in patients topically treated with multiple antiglaucoma BAK-preserved eye drops suggests a matrix metalloproteinase-related modification of conjunctival ECM remodeling. In vitro results suggest that CsA has the potential to limit BAK effects on EMMPRIN.